The New Anti-Patriarchy Crusades in the US: the Symbiotic Relationship between the Neo-Radical Feminism and the Alt-Right - Dahmani Thameur, Boussekra Bochra Rim (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
Abstract The political system of the USA during the existing Trumpismperiodknewfrequently, collapse between the radical feminism who claims to underminepatriarchy by transforming the entire structure of society, and the alt-right whorejects multiculturalism, and sees that the radical feminismprincipals threatenthe white supremacy civilization. The purpose of this study is to focus ontherelation between the radical feminism and the alt-right, and addressesthecontinuous conflict between the two major movements who have a hugeimpacton the American political system. In addition, it investigates howtheyemergedand increased to reach to the extreme level of conflict, Moreover, it explorestheimpact of each movement on the other, and the symbiotic relation that resulteddue to these conflicts, and how they rid up the mainstreamto achieveamagnificent impact on a large group of people. This study containstwochapters, the first one presents the theoretical background of each movementand its distinctive political approach, the second chapter containsthemanifestation of these theoretical approaches and the relation that emerged, andconsequently, became a necessity for both of them to guarantee their existence.
Keywords: Keywords: Radical Feminism, Alt-Right, Political System, Symbiotic Relation, Post Trump